Comparison of treatment retention and response to secukinumab versus tumour necrosis factor inhibitors in psoriatic arthritis. (26th December 2020) - Lindström, Ulf; Glintborg, Bente; Di Giuseppe, Daniela; Schjødt Jørgensen, Tanja; Gudbjornsson, Bjorn; Lederballe Grøn, Kathrine; Aarrestad Provan, Sella; Michelsen, Brigitte; Lund Hetland, Merete; Wallman, Johan K; Nordström, Dan; Trokovic, Nina; et al.
Abstract: Objectives: To compare treatment retention and response to secukinumab vs adalimumab, including the other four TNF inhibitors (TNFi) as comparators, in PsA. Methods: All patients with PsA starting secukinumab or a TNFi in 2015–2018 were identified in the biologic registers of the Nordic countries. Data on comorbidities were linked from national registers. One-year treatment retention and hazard ratios (HRs) for treatment discontinuation were calculated. The proportion achieving a 6 month 28-joint Disease Activity Index for Psoriatic Arthritis (DAPSA28) remission was determined together with odds ratios (ORs) for remission (logistic regression). Both HRs and ORs were calculated with adalimumab as the reference and adjusted for baseline characteristics and concurrent comorbidities. All analyses were stratified by the line of biologic treatment (first, second, third+). Results: We identified 6143 patients contributing 8307 treatment courses (secukinumab, 1227; adalimumab, 1367). Secukinumab was rarely used as the first biologic, otherwise baseline characteristics were similar. No clinically significant differences in treatment retention or response rates were observed for secukinumab vs adalimumab. The adjusted HRs for discontinuation per the first, second and third line of treatment were 0.98 (95% CI 0.68, 1.41), 0.94 (0.70, 1.26) and 1.07 (0.84, 1.36), respectively. The ORs for DAPSA28 remission in the first, second and third line of treatment were 0.62 (95% CI 0.30, 1.28), 0.85 (0.41, 1.78) and 0.74 (0.36, 1.51), respectively. In the subset of patients previously failing a TNFi due to ineffectiveness, the results were similar. Conclusion: No significant differences in treatment retention or response were observed between secukinumab and adalimumab, regardless of the line of treatment. This suggests that even in patients who have failed a TNFi, choosing either another TNFi or secukinumab may be equally effective.